Bearing the mercury burden for a rush of gold: The case of Mt. Diwalwal, Davo del Norte - Bondoc, Jonah L. (Animo Repository, 2013)
This review paper presents various studies and results of the degree of mercury contamination in the municipalities of Tagum, Compostela, Nabunturan, and Diwalwal, where some of the gold mining operations in Davao del Norte are located. Environmental samples such as air, water, sediment, and fish meat from the 4 municipalities have been tested. Results show that mercury intoxication on the island of Mindanao, a gold mining area, are probably partially due to exposures through the diet, especially for the non-occupationally burdened part of the population downstream from Mt. Diwalwal, where approximately a third (55 of 163) are intoxicated. Several studies revealed that the estimated total weekly MeHg intake for a person living in the area related to the weekly consumption of 2.1 kg of locally grown rice [15ug of methyl mercury (MeHg)], I kg of fish (220 ug MeHg), and 100g of mussels (50 ug MeHg), would total 285 ug MeHg (equivalent to 4.75 ug MeHG/kg bw. Some observed data gaps would include the total amount of metallic mercury entering the country; amount used by different sectors/applications. Further, in the small-scale mining sector, data must include all the other mining areas throughout the country. Data on mercury levels in river sediments should include all water bodies affected by mine tailings. There should be sufficient data on mercury release from all other uses and applications.